Roblox sebagai ruang sosial hibrid: Bagaimana roblox membangun pengalaman komunikasi anak-orang dewasa - Darmayunita, Nadia; Farida; M. Reza Ishadi Fadillah (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study examines patterns of children's interaction in Roblox gameplay, focusing on friendship formation, the use of digital symbols, and the social implications of gameplay. Using a qualitative netnographic approach, data were collected through observation and chat documentation of two popular maps: Brookhaven RP and the Mountain Climbing map. Thematic analysis indicates that children form friendships through spontaneous greetings, collaborative activities, and identity-related conversations, such as discussions of school levels. Digital symbols, emoticons, and slang are used to express closeness and build shared social meaning. The study also shows that virtual interactions enhance solidarity and empathy, but also trigger the absorption of adult cultural symbols that children do not fully comprehend.